2007
DOI: 10.2353/ajpath.2007.070073
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Liver Repair Mechanisms in Alagille Syndrome and Biliary Atresia Reveals a Role for Notch Signaling

Abstract: Patients with Alagille syndrome (AGS), a genetic disorder of Notch signaling, suffer from severe ductopenia and cholestasis, but progression to biliary cirrhosis is rare. Instead, in biliary atresia (BA) severe cholestasis is associated with a pronounced "ductular reaction" and rapid progression to biliary cirrhosis. Given the role of Notch in biliary development, we hypothesized that defective Notch signaling would influence the reparative mechanisms in cholestatic cholangiopathies. Thus we compared phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(131 citation statements)
references
References 52 publications
8
122
0
1
Order By: Relevance
“…Although mechanisms underlying these events are incompletely understood, biliary specification and/or morphogenesis are under genetic controls. For instance, defects in notch signaling pathways, hepatic transcription factors, and homoebox regulators, have been incriminated as primary genetic abnormalities in biliary specification and morphogenesis [42,43]. It should be noteworthy that our findings do not imply that cell adhesion molecules are causally significant in biliary development.…”
Section: Cell Adhesion and Organ Morphogenesismentioning
confidence: 53%
“…Although mechanisms underlying these events are incompletely understood, biliary specification and/or morphogenesis are under genetic controls. For instance, defects in notch signaling pathways, hepatic transcription factors, and homoebox regulators, have been incriminated as primary genetic abnormalities in biliary specification and morphogenesis [42,43]. It should be noteworthy that our findings do not imply that cell adhesion molecules are causally significant in biliary development.…”
Section: Cell Adhesion and Organ Morphogenesismentioning
confidence: 53%
“…Consistent with this, the extent of bile duct paucity varies with location in ALGS liver (7,52,53), and is most severe in the liver periphery (56). Based upon analysis of ALGS liver tissue, it has been proposed that altered Notch signaling impairs the formation of the distal branches of the biliary tree during the postnatal period in ALGS liver (57). We propose that the ALGS mutation specifically affects postnatal liver development, because this occurs when the liver precursor cells are no longer in contact with surrounding mesodermal tissue.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study revealed reduced hepatic fibrosis in patients with Alagille syndrome (AGS), a genetic disorder of Notch signaling, caused by mutations in the genes encoding Jagged1 or Notch2 receptor itself. 52 This was thought to be attributable to an accumulation of intermediate hepatobiliary cells unable to transdifferentiate into biliary cells because of the defective Jagged1/Notch2 signaling, which then proceeds with a form of fibrotic reaction characterized by thin septa and pericellular distribution. However, the effects on myofibroblast differentiation (from hepatic stellate cells) are not studied in these patients.…”
Section: Discussionmentioning
confidence: 99%